Diseño de plan de mantenimiento preventivo para el proceso de fabricación de borradores en la Empresa Carpincoop (2024)
The implementation of maintenance is of vital importance in the industry today, due to all its significant contributions to industrial processes, mainly in the quality and optimization of manufacturing processes, reducing machinery failures and, therefore, downtime. service, preserving assets for longer; All this entails economic benefits for the company. This is why the implementation of a maintenance plan executed according to the needs of the carpincoop company is proposed, it is established that it be preventive in nature in order to preserve the machinery in optimal operating conditions, reducing the most common failures in the same, improving availability and reliability in the development of their functions. The wood eraser manufacturing process was selected due to the various operations involved such as wood cutting, milling and sanding. The main machines available in the company intervene in this process, for the different wood transformation processes, being useful in all the company's production processes.